218k views
2 votes
What is (f+g)(x)?

f(x)=x^2−36

g(x)=x^3+2x^2−10



Enter your answer in the box.

What is (f+g)(x)? f(x)=x^2−36 g(x)=x^3+2x^2−10 Enter your answer in the box.-example-1

2 Answers

4 votes

Answer:


(f+g)(x)=x^(3)+3x^(2) -46

Explanation:

The given functions are


f(x)=x^(2) -36\\g(x)=x^(3)+2x^(2) -10

Now, the operation
(f+g)(x) indicates that we need to sum these functions. As polynomials, we can sum terms with equal grade. so,


(f+g)(x)=x^(3) +(2+1)x^(2) -10-36=x^(3)+3x^(2) -46

Therefore, the answer is
(f+g)(x)=x^(3)+3x^(2) -46

User Michael McTiernan
by
6.3k points
4 votes

Answer:

(f+g)(x) = x^3 + 3x^2 - 46.

Explanation:

(f+g)(x) means to add the like terms in each function together.

So (f+g)(x) = x^2 - 36 + x^3 + 2x^2 - 10 = x^3 + 3x^2 - 46

So (f+g)(x) = x^3 + 3x^2 - 46.

User Tommy Jinks
by
6.7k points